Working with links : Dreamweaver CS6 video quickstart. (Peachpit Press, 2012)
"Make site navigation elegant by taking advantage of Dreamweaver's versatility with links. You can create clickable graphics, links that open new windows or navigate to a precise spot on a page, and include an email address in a link."--Resource description page.